2019
DOI: 10.1186/s13019-019-1021-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative complications between segmentectomy and lobectomy by video-assisted thoracic surgery: a multicenter study

Abstract: Background Compared to lobectomy by video-assisted thoracic surgery (VATS), segmentectomy by VATS has a potential higher risk of postoperative atelectasis and air leakage. We compared postoperative complications between these two procedures, and analyzed their risk factors. Methods We reviewed the records of all patients who underwent anatomical pulmonary resections by VATS from January 2014 to March 2018 in two Swiss university hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 25 publications
4
39
2
1
Order By: Relevance
“…We found no differences with regard to intra‐ or postoperative outcomes between both groups. This corroborates previous work by our group and other multicentric studies, which compared postoperative VS and VL complications rates 34–37 …”
Section: Discussionsupporting
confidence: 92%
“…We found no differences with regard to intra‐ or postoperative outcomes between both groups. This corroborates previous work by our group and other multicentric studies, which compared postoperative VS and VL complications rates 34–37 …”
Section: Discussionsupporting
confidence: 92%
“…With the cancer screening and the wide use of LDCT, more and more patients tend to be younger [25]. Recently, some researchers suggested that postoperative complications are similar between the two procedures [26]. Therefore, whether segmentectomy can be safely and effectively applied to early NSCLC, surgical treatments require further research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a similar rate of complications was reported in a multicenter study that compared complications between VATS intentional segmentectomies and lobectomies. It also showed that the chest tube duration and the length of stay were shorter in the VATS segmentectomy group (6).…”
Section: Introductionmentioning
confidence: 90%
“…The inferior vein is dissected to expose its segmental branches. Care is taken to identify V 6 , which must be preserved. The inferior basal vein that drains V 9 and V 10 is cleared.…”
Section: S 9+10 (I) Ligamentum-based Approachmentioning
confidence: 99%